2018
DOI: 10.31983/keslingmas.v37i3.3881
|View full text |Cite
|
Sign up to set email alerts
|

Studi Hygiene Sanitasi Pengelolaan Makanan Dan Minuman Di Rsud Banyumaskabupaten Banyumas Tahun 2017

Abstract: AbstrakPengelolaan makanan di rumah sakit, sebagai bagian dari sistem pelayanan kesehatan di rumah sakityang mendukung upaya penyembuhan dan pemulihan penyakit melalui penyelenggaraan makanan yanghigienis dan sehat.Kualitas makanan harus terjamin terutama bagi pasien karena rentan terhadapberbagai penyakit termasuk penyakit-penyakit yang ditularkan melalui makanan.Tujuan penelitian iniadalah mengetahui skor sanitasi penerapan enam prinsip hygiene sanitasi pengelolaan makanan danminuman di instalasi gizi RSUD B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Table 4 shows an Rvalue (correlation coefficient) of 0.385, meaning that the level of relationship between food intake (X1), infectious diseases (X2), and environmental sanitation (X3) with the stunting category (Y) simultaneously had a low relationship. This study is similar to a study conducted by Kirana, et al (2016), which demonstrated that environmental sanitation (handwashing, food processing, and the quality of water sources) and knowledge were associated with the prevalence of stunting in toddlers in Rambah Health Center. 23 Several factors, including environmental sanitation, food processing, and the mother's awareness of stunting, can influence one of the causes of stunting.…”
Section: Relationship Between Food Intake Infectious Disease and Envi...supporting
confidence: 88%
See 2 more Smart Citations
“…Table 4 shows an Rvalue (correlation coefficient) of 0.385, meaning that the level of relationship between food intake (X1), infectious diseases (X2), and environmental sanitation (X3) with the stunting category (Y) simultaneously had a low relationship. This study is similar to a study conducted by Kirana, et al (2016), which demonstrated that environmental sanitation (handwashing, food processing, and the quality of water sources) and knowledge were associated with the prevalence of stunting in toddlers in Rambah Health Center. 23 Several factors, including environmental sanitation, food processing, and the mother's awareness of stunting, can influence one of the causes of stunting.…”
Section: Relationship Between Food Intake Infectious Disease and Envi...supporting
confidence: 88%
“…This study is similar to a study conducted by Kirana, et al (2016), which demonstrated that environmental sanitation (handwashing, food processing, and the quality of water sources) and knowledge were associated with the prevalence of stunting in toddlers in Rambah Health Center. 23 Several factors, including environmental sanitation, food processing, and the mother's awareness of stunting, can influence one of the causes of stunting. 23 Children under 5 years old will suffer from adverse effects on their health and nutrition from poor environmental sanitation.…”
Section: Relationship Between Food Intake Infectious Disease and Envi...supporting
confidence: 88%
See 1 more Smart Citation
“…Some sugarcane traders put raw sugarcane raw materials directly on the floor where they were traded without a base, the handlers did not wear gloves, did not wash their hands every time processing sugarcane juice, did not wear aprons, some traders wore gold jewelry and chatted while processing sugarcane raw materials.There is no running hand washing area available, some utensils are not washed before use, the utensils are not washed under running water and there are no covered bins. The results of this study are in line with research conducted by Sudariyono, R & Mulyasari, T, M (2018) regarding the hygiene and sanitation of catering services in the buffer area of the Class II Port Health Office of Tanjung Intan Cilacap, it is known that of the 5 food service businesses studied that meet health requirements there are 3 (three) catering service businesses.The results of research by Priyani, A & Budiono, Z (2017) show that the hygiene and sanitation of food and beverage processing at Banyumas General Hospital does not meet the requirements. Research by Ristoyo, R. et al (2016) of 16 respondents out of 30 respondents who have hygiene and sanitation behavior in processing does not meet the requirements.…”
Section: Discussionmentioning
confidence: 98%